Analysis of the Effect of Cost Accounting Information Systems, Technological Innovation, and Organizational Culture on Cost Efficiency in Manufacturing Companies in Surabaya - Judijanto, Loso; Sumantri, Sri (West Science Accounting and Finance, 2024)
This study investigates the relationships between key organizational factors—Cost Accounting Information System (CAIS), Technological Innovation, and Organizational Culture—and their impact on Manufacturing Efficiency. Utilizing quantitative analysis, the study examines an original sample of data from diverse industries. The hypothesis testing results reveal significant positive relationships between CAIS, Technological Innovation, Organizational Culture, and Manufacturing Efficiency. The findings underscore the importance of effective cost accounting systems, technological advancements, and positive organizational cultures in optimizing manufacturing processes. This abstract encapsulates the study's contributions, highlighting its implications for organizational decision-making and avenues for future research.